Sosialisasi Informasi Obat di TK. Nurul Iman Tanjungsari Tasikmalaya - Ruswanto, Ruswanto; Nofianti, Tita; Lestari, Tresna; Fathurohman, Mochamad (Jurnal Abdi Masyarakat (JAM), 2023)
The healing process in treatment is strongly influenced by adherence and accuracy in the use of drugs. In the community, both at school and in the family, understanding of information and drug use for parents, students, and teachers. The purpose of community service that has been carried out is to provide socialization and understanding of information and how to use drugs for teachers and parents of students. The method of implementing the activity is through socialization in the form of counseling about drug information. The organizers of the activity are lecturers and students of the Faculty of Pharmacy, Bakti Tunas Husada University, while the service participants are teachers and parents of kindergarten students of Nurul Iman. From the activities carried out, it can be concluded that the activities can run smoothly and can provide an understanding of information and how to use drugs for community service participants.